SOME REFLECTIONS ON GEORGE GAMOW'S CREATIVE STYLE - Pustylnik, I. B. (Одеські астрономічні публікації, 2017)
We discuss some aspects of the rich scientific legacy of George Gamow. Our analysis is based partly on Gamow's own scientific and popular books and articles, partly on reminiscences of his contemporaries. A special attention is given to G.Gamow's contribution to deciphering DNA genetic code and to the peculiarities of the "creative laboratory" of this unique figure in XXth century physics and cosmology.